Implementation of Sustainable Development in Girimekar Village Through Health Education in Waste Management - Nur Intan Hayati Husnul Khotimah; Mela Mustika Sari; Desi Wijayanti Eko Dewi; Intan Yusita; Mia Nisrina Anbar Fatin; Siti Adlin Nuryesa (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Waste management is important because waste and waste generated from human activities can be a source of disease. Garbage is a serious problem for society. In Cigiringsing village RW 16 Girimekar Village has a community called KSM Puspa Berdikari which has made every effort so that the volume of waste can be reduced, the efforts made still need support in terms of proper waste management and have a sale value and are safe for health. Proper management starts from the use of personal protective equipment when processing waste, sorting organic/inorganic waste and utilizing waste into goods of economic value. Inappropriate management can have a negative impact on health, therefore through KSM partners Puspa Berdikari health education is carried out as a form of implementing sustainable development through health education and waste management, namely processing waste into eco enzymes. This is done to improve public health and environmental quality which is closely related to the lifestyle and culture of the community itself and to make waste a resource that can be utilized in a sustainable manner. Therefore, waste management requires community participation. The most effective method used is promotive action in the form of counseling and simulations to provide learning experiences for individuals and communities in order to influence positive behavior in order to maintain, maintain and improve health so that it is effective in efforts to manage waste in a sustainable manner.